Edge‐Riched MoSe2/MoO2 Hybrid Electrocatalyst for Efficient Hydrogen Evolution Reaction. Issue 13 (5th February 2018) - Jian, Chuanyong; Cai, Qian; Hong, Wenting; Li, Jing; Liu, Wei
Abstract: Molybdenum diselenide (MoSe2 ) is widely considered as one of the most promising catalysts for the hydrogen evolution reaction (HER). However, the absence of active sites and poor conductivity of MoSe2 severely restrict its HER performance. By introducing a layer of MoO2 on Mo foil, MoSe2 /MoO2 hybrid nanosheets with an abundant edge and high electrical conductivity can be synthesized on the surface of Mo foil. Metallic MoO2 can improve the charge transport efficiency of MoSe2 /MoO2, thereby enhancing the overall HER performance. MoSe2 /MoO2 exhibits fast hydrogen evolution kinetics with a small overpotential of 142 mV versus RHE at a current density of 10 mA cm −2 and Tafel slope of 48.9 mV dec −1 . Abstract : MoSe2 )/MoO2 hybrid nanosheets with an abundant edge and high electrical conductivity can be synthesized on the surface of Mo foil by introducing a layer of MoO2 on Mo foil. Metallic MoO2 can improve the charge transport efficiency of MoSe2 /MoO2, thereby enhancing the overall hydrogen evolution reaction (HER) performance.